Aplicación de la norma internacional de auditoría NIA 220 en las empresas industriales del área de la construcción obligadas a auditoría externa en el Distrito Metropolitano de Quito por el periodo 2011 - 2012. - Reyes Araujo, Leonardo Andreé (2014)
This research will help us determine if the work performed by the external auditors is quality, and that the audited companies, in this case for purposes of the investigation will be taken as a sample construction companies are happy with the results reported by the auditors external. Construction companies are assessed to better understand their involvement and importance within the economy For purposes of research concepts as audit and the audit process itself, quality concepts and management indicators , which are the tools that were used to measure the quality of the audit obtained once the survey results are discussed, addition of International Financial Reporting Standards and International Accounting Standards as a key pillar in this globalized world, the International Auditing and Assurance as instructions or guidelines that will help the auditors to improve and provide quality service , also as a way to regulate the work performed by the audit team .